Answer:
(2,-5)
Step-by-step explanation:
See attachment
One can also solve this by calculation:
y=2x-9
y=-2x-1
-
Rearrange either equation to find x. I'll use the first:
y=2x-9
2x = y+9
x = (y+9)/2
Now use this value of x in the second equation:
y = -2x-1
y =-2((y+9)/2)-1
y = (-2y-18)/2)-1
y = -y -9 - 1
2y = -10
y = -5
Now use -5 for y in the rearranged equation:
y = -2x-1
-5 = -2x-1
-2x = -4
x = 2
Solution is (2,-5)
But the question wants a graph solution, which is also fun when you use DESMOS.
6(2x - 11) + 15 = 21
First step use distributive property on the left side to remove the parenthesis, to do this multiply 6 by each term inside the parenthesis:
12x - 66 + 15 = 21
Second step, simplify the left side by combining the like terms:
12x - 51 = 21
Third step, add 51 to both sides of the equation:
12x = 72
Last step, divide both sides by 12:
x = 72/12
x = 6
Answer:
m∠F = 66°
m∠D = 57°
Step-by-step explanation:
It looks like you have ...
∠D = ∠E = (4x +1)°
∠F = (5x -4)°
The sum of the angles in the triangle is 180°, so we have ...
2(4x +1) +(5x -4) = 180
13x -2 = 180
x = 182/13 = 14
Then the angle measures are ...
∠D = ∠E = (4(14) +1)° = 57°
∠F = (5(14) -4)° = 66°
__
m∠F = 66°
m∠D = 57°